A pilot study to determine the effect of weight bearing exercises and whole body vibration on gross motor function and spasticity in children with cerebral palsy - Honour, Amy Elizabeth Nicola (My University, 2014)
The aim of this study was to determine the effects of an eight-week weight bearing exercise program coupled with whole body vibration (WBV) on gross motor function, functional mobility and spasticity in hemiplegic type cerebral palsied school going children. The experimental group was compared to a control group undergoing the same exercise program. The control group excluded WBV training. Fifteen children participated in the study nine females and six males. There were eight children with right hemiplegia and seven with left hemiplegia; all children had gross motor classification (GMFCS) of Level 1. Significant improvements were seen in both groups for gross motor function. There was no difference in the amount of change seen between the two groups. A decline was noticed in the functional mobility assessment. The findings of this study demonstrated that both the children in the control and the experimental groups showed significant improvements in the GMFM scores after a weight bearing exercise program. The children in the experimental group who received WBV while exercising showed significant improvement from baseline to completion of the study compared to the group that did weight bearing exercise alone; better carry over effect in this group from WBV. Time up and down stairs (TUDS) and modified ashworth scale (MAS) scores showed less convincing results and need further investigation. Further research is required to determine the most effective and efficient way of managing children with cerebral palsy in a resource poor area.
Keywords: Cerebral Palsy--in infancy & childhood; Cerebral Palsy--therapy; Exercise Therapy